1990
DOI: 10.7557/2.10.2.797
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of reindeer with bovine viral diarrhea virus

Abstract: Two 8-month reindeer (Rangifer tarandus) and a 1-month-old Hereford-Holstein calf (Bos taurus) were inoculated intranasally with the Singer (cytopathogenic) strain of bovine viral diarrhea (BVD) virus. Clinical signs in reindeer included loose stools containing blood and mucus, and transient laminitis or coronitis. Signs in the calf were limited to bloody mucus in the stool and lesions in the nasal mucosa. Antibody titers to BVD virus in the reindeer were intermittent, and titers in the calf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“…Experimental infections in immunocompetent elk, mule and white-tailed deer, and reindeer showed no or only weak clinical signs but always transient viremia followed by seroconversion (Morton et al, 1990;Van Campen et al, 1997;Tessaro et al, 1999;Passler et al, 2007;Ridpath et al, 2007). Pregnant white-tailed deer, inoculated in early pregnancy by intranasal administration with infective doses, gave birth to offspring with persistent infection (Passler et al, 2007).…”
mentioning
confidence: 99%
“…Experimental infections in immunocompetent elk, mule and white-tailed deer, and reindeer showed no or only weak clinical signs but always transient viremia followed by seroconversion (Morton et al, 1990;Van Campen et al, 1997;Tessaro et al, 1999;Passler et al, 2007;Ridpath et al, 2007). Pregnant white-tailed deer, inoculated in early pregnancy by intranasal administration with infective doses, gave birth to offspring with persistent infection (Passler et al, 2007).…”
mentioning
confidence: 99%
“…106 In two young reindeer, loose, bloody, and mucoid feces, transient laminitis, or coronitis were observed after inoculation with BVDV Singer and mild lesions were detected at necropsy. 107 Naive white-tailed deer fawns developed moderate pyrexia and marked to moderate decreases in lymphocyte populations in response to either BVDV 1 or BVDV 2; and lethargy or coughing was observed in individual fawns. 108,109 Similar to other species, BVDV infections in wildlife may have the most important implications for reproductive health.…”
Section: Bvdv In Wildlifementioning
confidence: 99%
“…Transplacental infection leads to abortion, foetal malformations and development of persistently viremic calves depending on the state of development of the foetus and the biotype (cytopathogenic or non-cytopathogenic) of the virus (Moenning & Liess, 1995;Brownlie, 1990). It is unknown whether this applies to wild ruminants as well (Depner et al, 1991) although viremic individuals in wild ungulates were demonstrated by experimental infection (Morton et al, 1990;Hyera et al, 1993;Van Campen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs include weakness, lack of fear, impaired hearing and vision, dehydration and emaciation. Pyrexia, anorexia, salivation and nasal discharge usually also occur, while some cases have skin lesions and may be lame due to interdigital ulceration and inflammation of the coronary bands (Richards et al, 1956;Romvary, 1965;Wiesner, 1987;Neumann et al, 1980; Morton et al, 1990;Nettleton, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation